Fiscal decentralization and economic growth in selected European countries - Slavinskaitė, Neringa (Journal of Business Economics and Management, 2017)
The paper analyses the fiscal decentralization effects on economic growth in unitary countries of European Union for the period 2005–2014. The empirical analysis was based on the multiple regression method. The fixed effect panel model was used as framework for the analysis. In order to examine the different impact of fiscal decentralization, the same analysis was applied to subsets of countries categorized into two groups according to countries’ level of economic development. This further analysis found that there is positive relationship between fiscal decentralization and economic growth in low level of economically developing countries and no relationship in high level of economically developed countries. These results suggested that fiscal decentralization is not always instrument for promotion of economic growth, which means that country’s economic development level is an important factor when introducing reform of fiscal decentralization. The originality of this article – new fiscal decentralization index and evaluated fiscal decentralization level influence for countries economic growth.